Synthesis and structural characterization of polynuclear divalent ytterbium complexes supported by a bis(phenolate) cyclam ligand. (24th November 2016) - Maria, Leonor; Sousa, Vânia R.; Santos, Isabel C.; Mora, Elsa; Marçalo, Joaquim
Graphical abstract: A new [O2 N2 N′2 ] cyclam-based bis(phenol), H2 ( Me2 ArO)2 Me2 -cyclam, is described. The reaction of the potassium salt of this ligand with 1.5 and 2 equiv. of [YbI2 (thf)2.5 ] in thf led to the formation of the polynuclear Yb(II) complexes [Yb3 (μ-( Me2 ArO)2 Me2 -cyclam)2 I]I and [Yb2 (μ-( Me2 ArO)2 Me2 -cyclam)I2 (thf)2 ], respectively. Abstract: A new [O2 N2 N′2 ] 1, 4, 8, 11-tetraazacyclotetradecane-based bis(phenol) chelate, H2 ( Me2 ArO)2 Me2 -cyclam (2 ), containing methyl groups in the phenolate rings, has been synthesized and fully characterized. The studies of the coordination chemistry of the hexadentate dianionic ligands, ( R2 ArO)2 Me2 -cyclam 2− (R = t Bu, Me), with [YbI2 (thf)2.5 ] are reported. The reaction of K2 ( tBu2 ArO)2 Me2 -cyclam with [YbI2 (thf)2.5 ] in 1:1 ratio in thf led to the formation of a divalent ytterbium complex that is highly unstable and propitious to the formation of Yb(III) species, while the metathesis reaction of the less bulky ligand ( Me2 ArO)2 Me2 -cyclam 2− with [YbI2 (thf)2.5 ] showed a preference for the stabilization of polynuclear divalent ytterbium complexes. The reaction of the potassium salt of this ligand, K2 ( Me2 ArO)Me2 -cyclam, with 1.5 and 2 equiv. of [YbI2 (thf)2.5 ] in thf led to formation of [Yb3 (μ-( Me2 ArO)2 Me2 -cyclam)2 I]I (4 ) and [Yb2 (μ-( Me2 ArO)2 Me2 -cyclam)I2 (thf)2 ] (5 ), respectively. The trimer (4 ) and dimer (5 ) were characterized by elemental analysis, UV–Vis and NMR spectroscopy and single-crystal X-ray diffraction. These are the first examples of ytterbium(II) complexes incorporating bis(phenolate) cyclam ligands.